2007
DOI: 10.1111/j.1365-2575.2007.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing change in an information systems development organization: understanding developer transitions from a structured to an object‐oriented development environment1

Abstract: Object-oriented systems development has attracted great interest in the information systems (IS) field because of a belief that using object-oriented development (OD) makes it easier to develop and maintain software plus achieve software reuse. However, the transition from structured to OD may be especially challenging for IS developers. In fact, some argue that structured development (SD) knowledge may interfere with the ability to learn OD approaches because of a form of proactive interference.To understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Organizational unlearning is the process of replacing old patterns with new habits, beliefs, knowledge, and cognitive patterns ( Cegarra-Navarro et al, 2010 ; Akhshik, 2014 ; Hislop et al, 2014 ), which can effectively promote organizational learning and the absorption of new knowledge, and creatively adjust existing products and technologies through the integrated application of new and old knowledge to create new products to adapt to the new environment ( Hargadon and Sutton, 1997 ). Studies have found that in addition to reducing rigidity, organizational unlearning may promote the adoption of new knowledge and new technologies ( Carlo et al, 2011 ), and reduce the interference of existing cognition and conventions in organizations’ pursuit of innovation and new developments ( Shaft et al, 2008 ). In their study of the causes and consequences of unlearning in innovation teams, Akgün et al (2006) proposed that by adjusting beliefs and conventions and integrating them into their project, team members may use this new knowledge and information to significantly improve the success rate of developing new products and help their firm cope better with fierce market competition.…”
Section: Theoretical Analysis and Hypothesesmentioning
confidence: 99%
“…Organizational unlearning is the process of replacing old patterns with new habits, beliefs, knowledge, and cognitive patterns ( Cegarra-Navarro et al, 2010 ; Akhshik, 2014 ; Hislop et al, 2014 ), which can effectively promote organizational learning and the absorption of new knowledge, and creatively adjust existing products and technologies through the integrated application of new and old knowledge to create new products to adapt to the new environment ( Hargadon and Sutton, 1997 ). Studies have found that in addition to reducing rigidity, organizational unlearning may promote the adoption of new knowledge and new technologies ( Carlo et al, 2011 ), and reduce the interference of existing cognition and conventions in organizations’ pursuit of innovation and new developments ( Shaft et al, 2008 ). In their study of the causes and consequences of unlearning in innovation teams, Akgün et al (2006) proposed that by adjusting beliefs and conventions and integrating them into their project, team members may use this new knowledge and information to significantly improve the success rate of developing new products and help their firm cope better with fierce market competition.…”
Section: Theoretical Analysis and Hypothesesmentioning
confidence: 99%
“…Teresa Shaft, Leslie Albert and Jon Jasperson (Shaft et al, 2008) help us understand the complicated cognitive transition of IS developers as they change from a structured to an object-oriented development environment in order to take advantage of the ease of development and maintenance and support for software reuse claimed by object-oriented development. Four hypotheses are developed in the research, and these are tested through a…”
Section: Editorialmentioning
confidence: 99%
“…The comparison across the two industries illustrates the usefulness of the developed model. The authors conclude that the model shows that information processing requirements are a major influence on whether companies choose to be early and deep adopters of new technology.Teresa Shaft, Leslie Albert and Jon Jasperson (Shaft et al, 2008) help us understand the complicated cognitive transition of IS developers as they change from a structured to an object-oriented development environment in order to take advantage of the ease of development and maintenance and support for software reuse claimed by object-oriented development. Four hypotheses are developed in the research, and these are tested through a…”
mentioning
confidence: 99%
“…Most studies of cognition and system modelling and design have been based on positivist-style surveys (Lang and Fitzgerald 2007;Thomas and Bostrom 2007;Shaft, Albert et al 2008), or formal models (Wang and Fu 2004;Overbeek, van Bommel et al 2007) or normative theoretical studies (Gasson 2004;Nelson and Monarchi 2007;Siau and Wang 2007). Loucopoulos and Karakostas (1995) identified some factors affecting requirements specification as a problem solving activity as follows:…”
Section: Cognitive Processes In the Require-ments Engineering Processmentioning
confidence: 99%